2015
DOI: 10.1159/000431382
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Off-Line Extracorporeal Photochemotherapy in Patients with Chronic Lung Allograft Rejection Not Responsive to Conventional Treatment: A 10-Year Single-Centre Analysis

Abstract: Background: Extracorporeal photochemotherapy (ECP) for chronic lung allograft dysfunction (CLAD) has been reported as beneficial in a few short-term studies. Objectives: In this retrospective cohort study on 48 CLAD patients treated by ECP (off-line technique) for a period of >8 years (compared to 58 controls), we explored potential predictors of survival and response. Methods: Failures were defined as a decrease in forced expiratory volume in 1 s (FEV1) of >10% from ECP initiation. Results: ECP pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 24 publications
(45 reference statements)
3
38
0
Order By: Relevance
“…In the meantime, however, different CLAD phenotypes have been described that subsumes predominantly classic BOS and also RAS . A recent study has shown that CLAD patients non‐responding to macrolides and with non‐rapid kinetics of pulmonary function decline may benefit most from ECP therapy, and Del Fante and coworkers suggested a better response of ECP‐treated CLAD patients phenotyped as CLAD‐BOS as compared to RAS patients . Our data seem to be consistent with these findings.…”
Section: Discussionsupporting
confidence: 89%
“…In the meantime, however, different CLAD phenotypes have been described that subsumes predominantly classic BOS and also RAS . A recent study has shown that CLAD patients non‐responding to macrolides and with non‐rapid kinetics of pulmonary function decline may benefit most from ECP therapy, and Del Fante and coworkers suggested a better response of ECP‐treated CLAD patients phenotyped as CLAD‐BOS as compared to RAS patients . Our data seem to be consistent with these findings.…”
Section: Discussionsupporting
confidence: 89%
“…Further evidence about the impact of CLAD phenotypes on the effectiveness of ECP was recently reported (Del Fante et al , ). In this single centre experience of 48 recipients with CLAD, they concluded that although ECP reduced the rate of decline in FEV1 overall it was least effective in those with the RAS phenotype but that rapid loss of lung function in BOS was not associated with a poor response rate.…”
Section: Use Of Ecp In Thoracic Organ Transplantationmentioning
confidence: 87%
“…ECP treatment schedule for group A followed that one adopted in our centre for chronic lung allograft dysfunction (CLAD) patients: 12 1 cycle (that is, two apheresis sessions) per week for 3 weeks, 1 cycle fortnightly for 3 times, 1 cycle per month if improvement/stabilisation. For group B, immediately after the diagnosis of BOS, ECP cycles were intensified and followed the schedule described above for group A.…”
mentioning
confidence: 99%
“…The decision to increase the frequency of ECP sessions had been taken based on the good results obtained during our 10 years experience in treatment of CLAD in lung transplant recipients by ECP. 12 A possible explanation of the positive impact on BOS after ECP intensification may be the higher number of cells treated over time and consequently the more intense and lasting immunomodulation. Moreover, our results in the larger cohort of patients with CLAD treated by ECP are similar to those reported in the present study, thus suggesting that lung GvHD and BOS after lung transplantation are similar clinical and pathophysiological entities.…”
mentioning
confidence: 99%